PATHOGENICITY AND HISTOPATHOLOGICAL STUDIES ON THE NUCLEAR POLYHEDROSIS VIRUS OF THE FALL ARMYWORM, Spodoptera frugiperda (ABBOT & SMITH, 1797) (LEPIDOPTERA, NOCTUIDAE) - Garcia, M. A.; Andrade, C. F. S.; Lauritis, J.; Habib, M. E. M. (REVISTA DE AGRICULTURA, 2015)
PATHOGENICITY AND HISTOPATHOLOGICAL STUDIES ON THE NUCLEAR POLYHEDROSIS VIRUS OF THE FALL ARMYWORM, Spodoptera frugiperda (ABBOT & SMITH, 1797) (LEPIDOPTERA, NOCTUIDAE)